Antibiotic and antibiotic resistance genes in freshwater aquaculture ponds in China: A meta-analysis and assessment. (20th December 2021) - Wang, Cong; Liu, Xiaohui; Yang, Yuyi; Wang, Zhi
Abstract: Freshwater aquaculture is an important source, reservoir and hotpot of antibiotics and antibiotic resistance genes (ARGs), but the overall characteristics of antibiotics and ARGs in freshwater aquaculture on national scale is still unknown. This article is the first to comprehensively reveal the occurrence, distribution, trend and risk of antibiotics and ARGs in Chinese freshwater ponds through a meta-analysis. Results showed that forty-four antibiotics occurred in freshwater aquaculture ponds in China, and trimethoprim, enoxacin, monensin, clarithromycin, roxithromycin erythromycin-H2 O had the highest detection rates (>50%). Antibiotic concentrations in aquaculture ponds were related to the aquaculture area and aquaculture production at the provincial scale, and the pollution levels in Jiangsu and Tianjin were higher than that in other investigated provinces. Polymerase chain reaction results revealed that sul 1 and sul 2 were the most reported ARGs, and tetracycline resistance genes had the most reported subtype in aquaculture ponds. However, metagenomic results showed multidrug resistance genes were the predominant genes, followed by aminoglycoside, beta-lactam and bacitracin resistance genes. Meta-analysis showed that the significantly positive correlations existed in most antibiotics and their ARGs, e.g. ∑SAs with sul 2 and sul 3; ∑TCs with ∑ tet, tet A and tet O. Ecological risk assessment showed that 18 antibiotics in 27 evaluated antibiotics had medium-high risk levels in aquaculture waters. Antibiotic restriction programs have reduced the pollution level and ecological risks of target antibiotics in China to some extent. In order to pursuit the ecological and sustainable aquaculture, the future priorities and research direction on antibiotics and ARGs in freshwater aquaculture were finally pointed out. Graphical abstract: Image 1 Highlights: Forty-four antibiotics occurred in freshwater aquaculture ponds in China. Eighteen of the 27 evaluated antibiotics existed medium-high ecological risks. PCR and metagenomics results showed different ARG profiles and dominant ARGs. Antibiotics had significant correlation with aquaculture production and the ARGs. Antibiotic restriction programs reduced pollution and risk of target antibiotics.